Fingerprinting the Late Pleistocene tephras of Ciomadul volcano, eastern-central Europe - Harangi, Szabolcs; Molnár, Kata; Schmitt, Axel Karl; Dunkl, István; Seghedi, Ioan; Novothny, Ágnes; Molnár, Mihály; Kiss, Balázs; Ntaflos, Theodoros; Mason, Paul R. D.; Lukács, Réka (Journal of quaternary science, 2020)
Late Pleistocene tephras derived by large explosive volcanic eruptions are widespread in the Mediterranean and surrounding areas. They are important isochronous markers in stratigraphic sections and therefore it is important to constrain their sources. We report here tephrochronology results using multiple criteria to characterize the volcanic products of the Late Pleistocene Ciomadul volcano in eastern-central Europe. This dacitic volcano had an explosive eruption stage between 57 and 30 ka. The specific petrological character (ash texture, occurrence of plagioclase and amphibole phenocrysts and their compositions), the high-K calc-alkaline major element composition and particularly the distinct trace element characteristics provide a strong fingerprint of the Ciomadul volcano. This can be used for correlating tephra and cryptotephra occurrences within this timeframe. Remarkably, during this period several volcanic eruptions produced tephras with similar glass major element composition. However, they differ from Ciomadul tephras by glass trace element abundances, ratios of strongly incompatible trace elements and their mineral cargo that serve as discrimination tools. We used (U-Th)/He zircon dates combined with U-Th in situ rim dates along with luminescence and radiocarbon dating to constrain the age of the explosive eruptions of Ciomadul that yielded distal tephra layers but lack of identified proximal deposits.